Bacterial Infections and the Kidney - Satoskar, Anjali A.; Nadasdy, Tibor (Springer International Publishing : Imprint: Springer, 2017)
This text is designed to present a comprehensive and state-of the-art but practical approach to the diagnosis and management of bacterial infection associated renal disease. The chapters address the different types of glomerular, tubulointerstitial and vascular diseases, associated with bacterial infections, describe diagnostic pitfalls, provide differential diagnosis and discuss treatment and management. Easy to follow diagnostic algorithms and tables are included for practical usefulness. The text provides a large number of color microphotographs, illustrations and each chapter refers to the most important up to date literature in the area. All chapters are written by experts in the field and will include the most up-to-date clinical information. A comprehensive but user friendly resource on renal complications of bacterial infection, such as this book, is overdue, particularly now in the era of staphylococcus epidemic and emerging new resistant bacterial strains. Bacterial Infections and the Kidney will be an important resource for pathologists, nephrologists, general internists, infectious disease specialists, and urologists. Transplant surgeons may find the chapter on transplant pyelonephritis very useful.
Keywords: Medicine.; Nephrology.; Pathology.; Urology.; elektronické knihy; electronic books